Event-based tracking control for nonholonomic mobile robots. (November 2020) - Xie, Chen; Fan, Yuan; Qiu, Jianbin
Abstract: In this paper, we study the event-triggered control problem for a kind of nonlinear time-varying system. Generally speaking we use the Lyapunov stability theory to solve an event-triggered tracking control problem of non-holonomic mobile robots. Firstly, we propose a continuous tracking control law using nonlinear state feedback. Under some proper assumptions, we use the linearization technique to prove the exponential stability of the tracking system. Then, we propose an event-triggered controller for the robot and prove the uniform boundedness of the solutions by using the Gronwall–Bellman inequality. Moreover, it is shown that the solutions are uniformly ultimately bounded and there is no Zeno behavior in the tracking system. Simulation studies show the effectiveness of the proposed approach.